Soap-operas: identity and homosexuality representations: A case study of “Mulheres Apaixonadas” - Tonon, Joseana B. (2010)
The soap opera is seen by the most part of theBrazilian population as one of the mainproducts of the National television, specificallyif we talk about soap operas made by RedeGlobo de Televisão which owns the know-howto accomplish such productions. The presentarticle concerns about understand in whichmeans fictional identities representations arearticulated by the receptors during thereception process taking up a case study aboutwomen homosexuality representation played inMulheres Apaixonadas soap opera (ManoelCarlos, TV Globo, 2003) as research method.Supporting theoretical references are StuartHall on identity comprehension and MichelFoucault´s contributions on sexuality disciplinaryappliance properly comprehension concerningboth identities and subjectivities.